Identifikasi Parameter Signifikan Dalam Penentuan Prioritas Penanganan Banjir Kota Pekanbaru - Putra, Afdhal Suzalici; Sandhyavitri, Ari; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The effects of land conversion scheme from forest and agriculture areas to residential areas has significant result in reduction of water catchment areas, subsequently increasing the risk of floods. Therefore, it is necessary to identify significant parameters for flood mitigation. Flood mitigation parameters analyzed by using Decision Support System (DSS) is Analytical Hierarchy Process (AHP) and based on four criterias: technical, economic, environmental, and social/cultural.Based on the AHP analysis with Expert Choice 2000 program resulting in the percentage of most influential parameter criterias in determining flood mitigation priority that are technical criteria 57,0%, environmental criteria 18,7%, economic criteria 16,8%, and social/cultural criteria 7,5%. The most influential sub criterias are drainage system, construction cost and sub DAS rehabilitation, effect of land conversion, and the behavior of littering. Meanwhile percentage for sub DAS Pekanbaru city which become flood mitigation priority are sub DAS Sail 31,7%, sub DAS Senapelan 29,6%, sub DAS Air Hitam 20,9%, sub DAS Sibam 9,8%, and sub DAS Tenayan 8,0%.Key words : Analytical Hierarchy Process (AHP), Expert Choice 2000, Flood mitigation